Herbicidal activity of constituents isolated from Solanum elaeagnifolium (Solanaceae) - Mohamed Abdel aziz Balah (Journal of Crop Protection, 2015)
The bioactivity of chemical extracts from silverleaf nightshade Solanum elaeagnifolium Cav. seeds and leaves were tested for herbicidal activities, through water and ethanol extracts, against Portulaca oleracea L., Corchorus olitorius L., Convolvulus arvensis L.and Echinochloa crus-galli (L.) found in most Zea mays L.fields. Characterization of the isolated constituents from ethanol extract was conducted by various spectroscopic techniques. Purification of chloroform (100%) column fraction carried out by TLC plate using developing system; chloroform: ethanol: acetic acid (92:4:4) and hexane: chloroform: ethyl acetate (16:16:1) resulted chlorogenic acid, kaempferol and mangiferin. The second active column fraction eluted by chloroform: ethyl acetate was purified on TLC by chloroform: methanol: water (13:7:1) and butanol:water:formic acid (4:5:1) resulted in (coumaroyl glucoside, coumaroyl quince acid) and (kaempferol β-D-(6”-O-cis-cinnamoyl glucoside), dicaffeoyl quinic acids) respectively. The most active isolated component fromS. elaeagnifolium seeds was chlorogenic acid which decreased P.oleracea total biomass fresh weight by (86.5%) followed by kaempferol β-D-(6”-O-cis-cinnamoyl glucoside) (84.4%), while a moderate effect was achieved from coumaroyl glucoside (79.37%), mangiferin (76.98), kaempferol (72.48%) and coumaroyl quince acid (66.47%); finally the lowest activity (63.6%) was achieved by dicaffeoyl quinic acids compared with the controls. Thus, the herbicidal activity of these constituents suggests their potential for development as natural herbicides.